CONSTRUCTION METHOD OF ABILA PRECAST CONCRETE FOR HOUSING - Putranto, Rizky; Ariyansyah, Rona (Jurnal Teknik Sipil, 2022)
The purpose of this research is to arrange the stages of implementation of the ABILA precast concrete construction method to be applied to housing construction so that it can be used as a reference for future development. While the purpose of this research is to arrange the stages of housing construction with ABILA precast panels starting from the precast concrete production stage, transportation or mobilization of materials to the installation process and final completion. Precast concrete can speed up processing time, save costs, and minimize waste for formwork and scaffolding. In the world of construction, any waste of construction material must be reduced or even eliminated. The application of Precast Concrete is very easy, considering its plug and play nature. Besides being easy, precast concrete has quite a lot of applications, especially the Abila Panel which has a function as a building structure, it can also be used as fences, floors and drainage channels. The level of the implementation method for the development of precast concrete technology is divided into several levels between prefabrication, preassembly, and module. The implementation method of building a house with ABILA precast concrete takes 14 days in the field, starting from panel installation to finishing. The construction method includes prefabrication in the workshop, mobilization of panels to the job site, assembly of structural elements, installation of brick walls, installation of roof structures and roof coverings, electrical and mechanical floor work, installation of ventilation doors and windows and paint finishing.